CULTURE OF ENCOUNTER AND RECONCILED DIVERSITY: POPE FRANCIS’ VISION OF ECUMENISM - Joseph Xavier (Asian Horizons, 2017)
Pope Francis holds that the unity of Christians is an important element of our witnessing to the Gospel in the world. He cautions the Church against the temptation to be a ‘sect’ that insists on withdrawing from others. The Church needs to be a welcoming house of the Father with doors always wide open. In order to have a culture of encounter, he offers four principles that enhance unity. For him, ecumenical dialogue is a long-run historical process, which needs time and patience. Starting a process is more important than occupying spaces or achieving shortterm goals. Ecumenical dialogues must proceed with the conviction that unity will eventually prevail over conflicts. He encourages all Christians to appreciate diversity. Ecumenism is a journey, not a destination with predetermined objectives. Ecumenical dialogues must seek unity-in-diversity, not uniformity. For, the Christians must not resist the gifts of the Holy Spirit. In the ecumenical process, all should be ready to learn and appreciate the richness of others that may be mutually beneficial to all.